Pre-release Risk Assessments: Pilot Study of a Novel Tool in One Police Station in the North East of England. (22nd February 2022) - Lyall, Alicia; Austin, Helena; Alder, Ross; Wild, Georgina; Reid, Keith; McKinnon, Iain
Abstract: Research in police custody risk assessment and health screening has historically been focused on detainees arrival in custody with much less emphasis on pre-release risk assessment (PRRA). This research aimed to evaluate a modified PRRA piloted in one police station in the North East of England for two weeks in March/April 2019 against College of Policing's Authorised Professional Practice (APP) guidance. A controlled before and after study design was conducted. During the intervention phase, custody suite (A) piloted the modified PRRA whilst control custody suite (B) continued to use standard PRRA. Randomised, anonymised custody records were analysed; 300 records were taken from each suite during the intervention phase, and a further 300 from each suite during the period preceding intervention. PRRA records were scored against criteria derived from the College of Policing's APP guidance. Improvements were seen in seven outcomes with greatest effects observed in recording risks associated with mental health, physical health and substance misuse.